Prevalence of visual impairment in a rural community in Sri Lanka - Baminiwatta, N.M (My University, 1994)
A population based cross sectional prevalence survey of visual impairment was conducted in the area of divisional director of health services Rambukkana.1.Clinical component of the study included the testing of visual acuity, primary and special eye examination. 2.Knowledge of, attitudes shown and practices towards eye care. The data reveals that the overall prevalence of visual impairment is 10.94 per cent. The prevalence by low vision amounts to 9.6 and blindness 1.34 per cent respectively. There is no significant difference in the prevalence of visual impairment between males and females.(Females 6.7 per cent and male 4.2 per cent) The study has also revealed that the monocular visual impairment amounts to 5.57 per cent (low vision 4.6 per cent and blindness 0.96 per cent) and the binocular visual impairment as the 9.4 per cent (low vision 7.1 per cent and blindness 2.3 per cent). Compared with monocular blindness (0.96 per cent). There is a much greater prevalence of bilateral blindness(2.3 per cent) in the sample. The prevalence is increased with age, peaking in the older age group. Un operated cataract was responsible for 33.3 per cent of visual impairment and uncorrected aphakia was seen in 7.8 per cent. Other causes of visual impairment were, squint(3.8 per cent). Retinopathy (2.6 per cent) Degenerative changes (2.6 per cent) and Glaucoma (1.2 per cent). The overall knowledge in eye health seems to be satisfactory. The mean score obtained was 60.3 per cent. The attitude towards consanguinity and squint are not favorable. Most of the sample population (86.7 per cent) seek western medical treatment as their first preference. The study has revealed that a backlog of visually impaired people are trapped in the rural village and it suggests that the eye care services has to be extended much more in to the rural community